2018
DOI: 10.1002/fsh.10054
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Conservation Potential of Tributaries for Native Fishes in the Upper Colorado River Basin

Abstract: We explored the conservation potential of tributaries in the upper Colorado River basin by modeling native fish species richness as a function of river discharge, temperature, barrier‐free length, and distance to nearest free‐flowing main‐stem section. We investigated a historic period prior to large‐scale water development and a contemporary period. In the historic period, species richness was log‐linearly correlated to variables capturing flow magnitude, particularly mean annual discharge. In the contemporar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
34
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 45 publications
4
34
0
Order By: Relevance
“…Laub et al. () suggested that the natural flow and thermal regimes in smaller Colorado River tributaries could support the ecological processes—which have been severely altered and are more difficult to restore in main‐stem rivers—that are necessary for the maintenance of large‐river species. While we must recognize recent exceptions, such as the resurgence of native fishes in much of the Colorado River in Grand Canyon (Kegerries et al., in press), climate change is expected to further constrain streamflow (Udall and Overpeck ), which could accelerate the replacement of native fishes by nonnative species (Ruhí et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Laub et al. () suggested that the natural flow and thermal regimes in smaller Colorado River tributaries could support the ecological processes—which have been severely altered and are more difficult to restore in main‐stem rivers—that are necessary for the maintenance of large‐river species. While we must recognize recent exceptions, such as the resurgence of native fishes in much of the Colorado River in Grand Canyon (Kegerries et al., in press), climate change is expected to further constrain streamflow (Udall and Overpeck ), which could accelerate the replacement of native fishes by nonnative species (Ruhí et al.…”
Section: Discussionmentioning
confidence: 99%
“…). Havasu Creek has considerably smaller discharge than the suggested thresholds for tributaries with conservation potential for large river fishes (~25 m 3 /s; Laub et al ()), but flows and water temperatures are relatively unimpaired, exhibit characteristics that are consistent with those of spring‐fed perennial arid‐land rivers, and are reliable and consistent during base flows (Melis et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…; Laub et al. ). While these studies focused primarily on perennial tributaries, in some instances with enhanced flows resulting from irrigation projects, our study focused on a stream that is dry for a majority of the year.…”
Section: Discussionmentioning
confidence: 97%
“…; Laub et al. ; Hooley‐Underwood et al. ), most studies do not explore how small tributaries may affect main‐stem distributions of fishes.…”
mentioning
confidence: 99%
“…For example, small tributaries in the Colorado River basin retain larvae (Haynes et al 1984), offer productive subadult growth (Webber et al 2012), connect habitats for spawning migrations (Weiss et al 1998), and provide refugia or foraging outside of mainstem environments (Cathcart et al 2018a). While tributary systems are recognized as crucial habitats for native desert fishes (Fraser et al 2017;Laub et al 2018;Hooley-Underwood et al 2019), most studies do not explore how small tributaries may affect main-stem distributions of fishes. This perspective is important because tributary systems and their junctions with main-stem rivers impart strong ecological forces that spatially structure fish populations (Fernandes et al 2004;Lopes et al 2019), communities (Osborne and Wiley 1992), and geomorphological processes throughout river networks (Benda et al 2004;Kiffney et al 2006).…”
mentioning
confidence: 99%